Outdoor light spending time, genetic predisposition and incident Parkinson’s disease: the mediating effect of lifestyle and vitamin D - Yumei Huang; Shufan Tian; Kangli Qiu; Jinchi Xie; An Pan; Gang Liu; Yunfei Liao (Journal of Health, Population and Nutrition)
Abstract Background Previous studies suggest that outdoor sunlight exposure was associated with a lower risk of Parkinson’s disease (PD). However, the interaction of genetic predisposition and the potential role of lifestyle risk factors in mediating this association remains unclear from prospective evidence. Methods A cohort study based on the UK Biobank enrolled participants between 2006 and 2010, with the latest follow-up in November 2022. In the prospective population-based study 375,599 UK adults aged 37–73 years were enrolled. The outdoor light time was assessed using a questionnaire survey to investigate how many hours were spent outdoors on typical summer and winter days. New-onset PD was identified through linkage with inpatient hospitalization and death registers. Multivariate Cox proportional hazard regression models were used. The polygenic risk score (PRS) for PD comprised 44 single-nucleotide variants. The mediation analysis of lifestyle risk factors and vitamin D on this association was performed. Results A total of 375,599 participants (mean age, 56.8 years; 46.3% males) were included, and 2,824 individuals were first-ever diagnosed with PD. Compared with the individuals with shorter outdoor light time, those with longer time in summer (HR 0.77; 95% CI, 0.68–0.88), in winter (HR 0.85; 95% CI, 0.75–0.96), and on average (HR 0.83; 95% CI, 0.73–0.93), were prone to have lower PD risk. There was a joint association between outdoor light time and genetic predisposition in PD incidence, and higher genetic risk of PD could be modifiably decreased through longer outdoor light exposure. In mediation analyses, physical activities mainly explained 15.83% on average, while the mediating effects of sleep patterns (2.71%) and vitamin D (4.91%) were relatively mild of the association between outdoor light time and PD, respectively. Conclusion In this cohort study, a longer duration of outdoor sunlight exposure was associated with a lower risk of PD, and was more pronounced in individuals with high genetic risk. This association was partly mediated by physical activity, sleep patterns, and vitamin D. These findings highlight the potential of promoting regular outdoor activities as a practical strategy to mitigate PD risk, especially among genetically susceptible individuals.